Science and Society in Ireland: Examining Public Trust in Scientists against a Global Background - Roche, Joseph; Hurley, Mairad; Taylor, Aoife (My University, 2025)
Public trust in scientists is vital for navigating complex global challenges, influencing evidence-informed policy, and promoting societal well-being. However, concerns exist about a potential crisis of trust in science, fuelled by misinformation, conspiracy theories, and science-related populism. The Trust in Science and Science-Related Populism (TISP) study investigated public perceptions of scientists across 68 countries. This paper examines the TISP findings for Ireland, focusing on public trust in scientists and the implications for the Irish educational landscape. The study reveals that trust in scientists in Ireland is generally moderate to high, exceeding global averages, but notably lower among younger respondents. Regression analyses show a strong association between trust in scientific methods and overall trust in scientists, highlighting the importance of robust science education with a strong emphasis on science communication. Qualitative analysis of open-ended responses reveals a strong expectation that scientists should embody professionalism, integrity, and continuous self-improvement. These findings suggest a need for targeted science education and communication efforts in Ireland, emphasising critical thinking skills, understanding of the scientific process, and the ethical responsibilities of scientists. Promoting transparency, dialogue, and public participation in scientific endeavours will help foster a more robust and trusting relationship between science and society in Ireland.
PUBLISHED
Keywords: Trust in scientists, science communication, science education, public engagement with science, survey; SCIENCE COMMUNICATION; TRUST; public understanding of science